Production of cracker biscuits using high-protein Australian Noodle Wheat (ANW). (November 2021) - Siah, Siem; Kennett, Andrew; Ma, Wujun; Diepeveen, Dean; Mullan, Daniel
Abstract: Australian Noodle Wheat (ANW) is soft-grained wheat primarily grown to suit the production of Japanese udon noodles. ANW with grain protein content above 11.5% (11% m.b.) is classed as ANW2 and traded at a discounted price due to no specific end-use. This study hypothesizes that off-graded ANW2 is suitable to produce cracker biscuits. Evaluation of ANW with 9.7–15.0% protein content shows that those above 11.5% make crackers with higher stack height and lower checking rates. ANW extensibility (r = 0.5, p < 0.05) and development time (r = 0.7, p < 0.01) correlate positively with stack height. The raw dough weight correlates negatively with checking (r = −0.8, p < 0.001), but positively with glutenin (r = 0.5, p < 0.05), α/β-gliadins (r = 0.6, p < 0.05), maximum resistance (r = 0.6, p < 0.05) and development time (r = 0.6, p < 0.01). The α/β-gliadins, maximum resistance and development time correlate negatively (r = 0.5, p < 0.05) with checking. The cracker qualities are not related to glutenin to gliadin ratio, proportions of ω- and γ-gliadins and unextractable polymeric protein. ANW with high protein content contributes to the high extensibility with adequate dough strength required to achieve good cracker stack height while favorably lowering checking rates. ANW2 containing 12–13.0% protein content is ideal for cracker making. This study shows the advantage of applying downgraded ANW in crackers; this may increase its value and benefit the farming industry and biscuit manufacturers. Graphical abstract: Image 1 Highlights: High-protein Australian Noodle Wheat (ANW) is suitable to produce cracker biscuits. ANW with 12–13% grain protein content (11% m.b.) is ideal for making crackers. ANW makes crackers with high stack height and low checking rates. α/β-gliadins correlates negatively with checking. High extensibility and adequate dough strength result in good quality crackers.